Adenomatoid odontogenic tumour: a case study with radiographic differential diagnostic considerations. - Siar, C.H.; Ong, S.T.; Ng, K.H. (1996)
Adenomatoid odontogenic tumours (AOT) are benign, hamartomatous odontogenic lesions that not uncommonly mimic a dentigerous cyst radiographically. Such a case as found involving an unerupted left maxillary canine in a 19-year-old Chinese female is described. The differential diagnosis of some common odontogenic cysts and neoplasms occurring in Malaysians, that may present in a dentigerous relationship to an unerupted tooth is discussed. A brief review of the radiographic literature on AOT is also included.